From trustworthiness to secular beliefs: changing concepts of xin 信 from traditional to modern Chinese - Meyer, Christian; Clart, Philip (Religion in Chinese societies, 2023)
"What does the Chinese term xin mean? How does it relate to the concept of faith in a Western sense? How far does it still denote "being trustworthy" in its ancient Confucian sense? When did major shifts occur in its long history of semantics that allowed later Christian missionaries to use the term regularly as a translation for the concept of believing in gods or God? This volume offers a broad picture of the semantic history of this Chinese term, throwing light on its semantic multi-layeredness shaped by changing discursive contexts, interactions between various ideological milieus, and transcultural encounters"--
Keywords: Aufsatzsammlung; Geschichte; Xin; Philosophie; China; Semasiologie; xin; Substantiv; Chinesisch